Effective Techniques for Teaching English Grammar to Young Learners - O'ktamova Shaxrizoda Alisher qizi (European Science Publishing, 2023)
English has witnessed a surge in popularity as the most widely studied language worldwide due to the extensive opportunities it presents for individuals who possess proficiency in the language. While adults generally face fewer obstacles when acquiring English proficiency, grammar comprehension can pose particular difficulties for younger learners.Therefore,it is essential for teachers to possess knowledge of effective and beneficial strategies to deliver lessons in a manner that accommodates the specific needs of these young learners.
Keywords: grammar,young learners, Scaffolding, systematic guidance,structures, pedagogical games, grammar-focused board games, visual aids feedback, grammatical errors, student engagement, humorous narratives.